A settling model for full-scale aerobic granular sludge. (1st November 2020) - van Dijk, Edward J.H.; Pronk, Mario; van Loosdrecht, Mark C.M.
Abstract: The settling behavior of aerobic granular sludge (AGS) in full-scale reactors is different from the settling of normal activated sludge. Current activated sludge models lack the features to describe the segregation of granules based on size during the settling process. This segregation plays an important role in the granulation process and therefore a better understanding of the settling is essential. The goal of this study was to model and evaluate the segregation of different granule sizes during settling and feeding in full-scale aerobic granular sludge reactors. Hereto the Patwardhan and Tien model was used. This model is an implementation of the Richardson and Zaki model, allowing for multiple classes of particles. To create the granular settling model, the most relevant parameters were identified using aerobic granular sludge from different full-scale Nereda® reactors. The settling properties of individual granules were measured as was the bulk behavior of granular sludge beds with uniform granular sludge particles. The obtained parameters were combined in a model containing multiple granule classes, which then was validated for granular sludge settling in a full-scale Nereda® reactor. In practice a hydraulic selection pressure is used to select for granular sludge. Under the same hydraulic selection pressure the model predicted that different stable granular size distributions can occur. This indicates that granular size distribution control would need a different mechanism then the hydraulic selection pressure alone. This model can be used to better understand and optimize operational parameters of AGS reactors that depend on granular sludge size, like biological nutrient removal. Furthermore insights from this model can also be used in the development of continuously fed AGS systems. Graphical abstract: Image 1